The 5-year incidence of type 2 diabetes mellitus in women older than 15 years in Ankara, Turkey: A population-based study - (:unkn) unknown (BMJ Publishing Group, 2010)
Background: Type 2 diabetes mellitus (DM) is a significant cause of morbidity and premature mortality especially in adults. In Turkey, there are few studies on DM incidence. This study aimed to determine the incidence of type 2 DM in women 15 years or older in Turkey. Methods: This prospective cohort study was performed from December 2002 to May 2003. Preliminary population-based screening was performed in 1997 and 1998 on women 15 years or older living in 4 villages in the Gölbaşi, Ankara province. Five hundred sixty-three women who were considered nondiabetic in the first study comprised the population for the present study. Data collection was accomplished by using a questionnaire and randomly measuring the blood glucose levels of the women. The χ2 and Fisher exact tests were used to analyze the risk factors for DM. Results: The 5-year incidences of type 2 DM, impaired glucose tolerance, and impaired fasting glucose were 2.3%, 0.4%, and 0.7%, respectively. The 5-year incidence of type 2 DM increased with age (P < 0.05). The DM incidence was 6.2% in those with mixed-type hypertension and 4.0% in those with a body mass index of 30 kg/m2 or higher. At 5-year follow-up, age (≥35 years), hypertension, and body mass index (≥30 kg/m2) were the risk factors for incidence of abnormal glucose metabolism (P < 0.05). Conclusions: The incidence of abnormal glucose metabolism in this study is in accord with that in the literature. Our results will contribute to our understanding of the incidence of DM in women in Turkey. Copyright © 2010 by The American Federation for Medical Research.
Keywords: Diabetes mellitus; Incidence; Turkey; Women